Análisis del perfil y motivación del turista que visita la ciudad de Latacunga en la festividad de la Mama Negra del mes de noviembre del 2023 - Ponce Tasgacho, Jessica Estefania (2024)
The current research project was developed in the Latacunga city in the Cotopaxi province, having as aim by analyzing the tourist profile and motivation, who visits the Latacunga city during the Mama Negra festival in November, which used a descriptive level methodology with a qualitative approach. In the first aim, it was made the Mama Negra festival description, the collected information was, by means bibliographic reviews and interviews; resulting in the fact, which the Mama Negra festival in November has been taking place since 1964, and emerge as a parody to the celebration in September, taking place on the November first Saturday before the celebration for the city independence, it walks through the different streets to the troupe’s rhythm from participating institutions. The second aim is to identify the tourist profile and motivation, where was applied a descriptive research type, with the survey technique, where was made a population sampling based on the tourists number, who enter the Cotopaxi National Park and the Quilotoa Lagoon, being 355,389 in total, it was applied the formula for sampling, resulting in 384 surveys, the instrument by collecting information was structured with 4 variables (demographic, socioeconomic, motivational and satisfaction), thus determining, what the tourists who arrive 97.66% are Ecuadorians, ages of 21 to 30 years old, coming from the Quito city with the 26% due to its proximity, with a men high rate, who visit Latacunga. Their trip way, they travel is as a family, by spending on average about 30 dollars. The tourists occupation is 38.67% students, having as main reason, it is to reunite with family and friends. In the third aim, it was applied a descriptive research type with a qualitative approach, it was elaborated the academic article, locating summarized way, the got results in the research, according to the structure by the Ciencia Digital magazine, which is based on contributing to the professionals training, who are capable by critically exposing the results determined in their researches. Concluding, which the Mama Negra of November month has an important value for its people, due to it allows them to meet again with family and friends, the majority tourists are local residents from city or in other nearby cities.